4-[4-(4-Methoxyphenyl)-1, 3-butadienyl]-1-methylpyridinium 4-chlorobenzene sulphonate (MBMPCBS) – an efficient nonlinear optical crystal with superior thermal stability. Issue 17 (6th April 2023) - Arul, Anand; Ramaclus, Jerald Vijay
Abstract : Influence of the methoxy functional group and increased π conjugation length of the chromophore for enhancing the thermal stability and NLO properties. Abstract : Organic crystals are considered to be one of the best THz emitters due to their high nonlinear optical susceptibility but are thermally fragile and vulnerable to damage when exposed to high power lasers during THz generation. Therefore, a novel molecule, 4-[4-(4-methoxyphenyl)-1, 3-butadienyl]-1-methylpyridinium 4-chlorobenzene sulphonate with methoxy as a functional group and an elongated π conjugation length is designed in order to create an organic crystal with good thermal stability, as well as large nonlinear optical properties. The synthesized molecule is developed into single crystals by studying their solubility in various solvents. The crystal structural properties of the crystal are investigated via single-crystal X-ray diffraction. The average polarizability, polarizability anisotropy, 1st hyperpolarizability, and 2nd hyperpolarizability values of MBMPCBS are determined to be 1.2 times higher than those of DAST. The second harmonic generation efficiency is found to be 16 times more than that of DAST. The crystal possesses a very large thermally stable region at 110 °C. The origin of high optical nonlinearity and thermal stability is investigated by analyzing the intermolecular and intramolecular interactions.